Analisis Sebaran Spasial Kerawanan Penyakit Demam Berdarah Dengue Tahun 2010 – 2019 di Kota Banda Aceh - Asniati Asniati; SM Indirawati; B Slamet (Fakultas Teknik, 2021)
Banda Aceh City is one of the dengue-endemic area. During a 10 year period (2010 - 2019), the total number of cases of Dengue Hemorrhagic Fever (DHF) in Banda Aceh City was 3,168 cases with a total of 16 deaths. Thus, it is necessary to map the vulnerability of dengue in Banda Aceh City. The purpose of this study was to map the distribution of dengue-prone areas in the city of Banda Aceh. The parameters used in the study were rainfall, air temperature, humidity, and population density. This parameter is used because it is considered to have a close relationship to habitat for the development of the Aedes aegypti mosquito. Secondary data were collected from the Central Statistics Agency (BPS), the Meteorology, Climatology and Geophysics Agency (BMKG), the Regional Development Planning Agency (Bappeda), the Marine and Fisheries Agricultural Food Service (DPPKP), and the Banda Aceh City Health Office from 2010 - 2019 shows that dengue cases correlate with rainfall of 25.07%. DHF cases correlate to humidity, which is 42.06%. Meanwhile, the correlation between temperature and DHF cases was -47.26%. The results of the spatial analysis of DHF vulnerability show that dengue is highly vulnerable in Jaya Baru District, Baiturrahman District, Kuta Alam District, and Syiah Kuala District